Spin transport in scalable graphene spintronic devices - Göransson, Marcus (My University, 2025)
Spintronics is considered as one of many technologies used to go Beyond Moore’s law and has special interest within information storage and processing. The performance of spintronic devices are dependent on the spin properties of its spin transport layer and the spin injection and detection efficiency. Ever since the discovery of graphene 2D materials has been of interest for spintronics, where previous research has concluded that graphene has excellent spin transport properties. Spin current can be injected and detected using a magnetic material, where previous research has found using a ferromagnet for this purpose together with a tunnel barrier creates contacts with high spin injection/detection efficiency. In this thesis, spintronic devices were designed and fabricated using graphene as spin transport layer together with Co/TiO2 contacts. Current bias, channel length, channel width and contact width were investigated by measuring both non-local (NL) spin valve and NL Hanle precession measurements to extract spin parameters: voltage amplitude (ΔVNL), spin diffusion length (λS), spin diffusion constant (DS) and spin lifetime (τs) and then analysing the parameters dependence of investigated factors. On top of this, Hanle spin angle φ were also measured to determine the angle of measured spin current. The project was successful in measuring spin signals for uniform and non-uniform spintronic devices with channel width between 1 − 3 μm. It was concluded that ΔVNL has a linear current bias dependence while none of the other spin parameters showed any current bias dependence. It was concluded that more measurements are needed to draw any conclusion about channel length, channel width or contact width dependence.
Keywords: Spintronics, Graphene, Beyond Moore’s law, 2D materials, Spin valve, Hanle precession, Room temperature